Ethical Considerations in Educational Technology : Balancing Innovation and Responsibility - SantoshKumar Pulijala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the rapid advancement of educational technology and its ethical implications. It examines key technological innovations such as Artificial Intelligence, Virtual and Augmented Reality, and Learning Management Systems, highlighting their potential to transform learning experiences. The article addresses critical ethical considerations including privacy and data protection, equity and access, transparency and accountability, and digital well-being. By analyzing these concerns, the article proposes strategies for responsible implementation of educational technology and provides specific recommendations for policymakers, educators, and technology developers. The article emphasizes the importance of balancing technological innovation with ethical practices to create an equitable, transparent, and effective educational ecosystem in an increasingly digital world.
Keywords: Educational Technology; Ethical Considerations; AI in Education; Data Privacy; Digital Equity